Anticoagulation and Monitoring of a Novel and Reversible Factor IXa Inhibitor. Issue 8 (31st October 2013) - Becker, Richard C.; Chan, Mark Y.; Vavalle, John P.; Povsic, Thomas J.; Gurwitz, David
Abstract <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> Clinical Development Phases I‐III Regulatory, Quality, Manufacturing </table-wrap> Thrombosis as a clinical phenotype is ubiquitous in human diseases and conditions, ranging from atherosclerosis and other vascular disorders to trauma, surgery, malignancy, infections, blood dyscrasias, auto‐immunity, and complications of pregnancy. While each condition carries its own distinct signature and predisposition for thrombosis as a nonphysiological event, there are several common themes that center on cellular and noncellular elements, including well‐characterized coagulation proteases. Over the past decade, our group has been actively involved with the development of a factor IXa inhibitor, pegnivacogin, and its complementary antidote or control agent, anivamersen. The following review provides a summary of fundamental constructs, milestones, and the current status of our translational journey.